Going below zero - How do banks react? - Henrike Michaelis (Deutsche Bundesbank, 2022)
Exploiting confidential data on individual German bank balance-sheets, I analyse what characterises a bank that opts to apply negative interest rates to corporate deposits. The results suggest that banks that are highly exposed to the negative interest rate policy (NIRP), i.e. funded by a larger share of household deposits, are more likely to apply negative corporate deposit rates. Furthermore, I examine whether banks adjusted their fee and commission strategy during the NIRP period and if they do what characterises those banks. My results show that banks adjusted their strategy in deposit business with households during the NIRP period. Compared with before, they generated higher net commission income on their outstanding household deposit holdings.
Keywords: E52; E43; E44; E58; G20; G21; 330; Monetary policy transmissions; negative rates; deposits; excess liquidity; interest rate pass-through; fees and commissions